Foreign policy - Hossain, Ishtiaq (Cengage Learning Asia Pte Ltd., 2008)
This chapter provides a broad view of Malaysia's foreign policy. It applies the "funnel of causality" to explain the various factors that shape the foreign policy of Malaysia. This is followed by an analysis of the aims and objectives of Malaysia's foreign policy. Finally, it provides a survey of foreign policy of Malaysia under the leadership of Prime Ministers Tunku Abdul Rahman 0957-1970), Tun Abdul Razak bin Hussein 0970-1976), Tun Hussein Onn (1976-1981), Tun Dr. Mahathir Mohamad (1981-2003), and Data' Seri Abdullah bin Haji Ahmad Badawi (2003- ).